Metode Dakwah dalam Mengatasi Perilaku Menyimpang Remaja di Mendahara Ilir - Agus; Jamaluddin; Edy Kusnadi (Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2020)
This research is motivated by a phenomenon that occurs in Mendahara Ilir Village, Mendahara District, East Tanjung Jabung Regency, that teenagers in this village behave inappropriately such as stealing, drinking, gambling, drugs and smoking, which makes parents and the surrounding community restless. . Then the author relates this phenomenon to the da'wah method carried out by the local da'i, whether his da'wah has had an effect or not. The research method used is descriptive qualitative field research, which describes the da'wah method in overcoming deviant behavior in adolescents. The results of the study show that the da'i method of da'i is the bil oral method and gathers youth in hadroh art groups. Teenagers in the Mendahara Ilir village seem to reduce their deviant activities. A good da'wah method for teenagers can encourage teenagers to do positive activities such as practicing hadrah, teaching hadroh to other friends, actively attending taklim assemblies, actively asking questions, polite in speaking, although not involving all teenagers in this village. However, this method can be said to be quite effective in overcoming deviant behavior in adolescents.